(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND Secondary hyperparathyroidism is common in patients with end-stage chronic kidney disease. If drug therapy fails, total parathyroidectomy with autotransplantation of parathyroid tissue into the forearm (PTX-AT) is the most widely used procedure. High recurrence rates of secondary hyperparathyroidism following PTX-AT are reported in the literature. OBJECTIVE The aim of this study was to evaluate recurrences of secondary hyperparathyroidism following PTX-AT in detail in order to develop strategies to prevent recurrences in the future. METHODS This retrospective study analysed a single-centre cohort of 42 patients who underwent PTX-AT for secondary hyperparathyroidism at a tertiary centre in Switzerland. Postoperative PTH levels were evaluated to determine the recurrence and persistence rates and the time to recurrence. Furthermore, the peri- and postoperative outcomes were assessed. Patients on dialysis and patients with a functioning kidney transplant suffering tertiary HPTH were analysed separately. RESULTS Intraoperative measurements showed that serum PTH decreased to 6.9% (3.3–15.0%) of the preoperative baseline level. After a median follow-up of 89.5 months (IQR 31.9–152.9), persistence of secondary hyperparathyroidism was found in five patients (11.9%) and recurrence in four patients (9.5%), giving a total recurrence rate of 21.4%. CONCLUSION Recurrence of secondary hyperparathyroidism after PTX remains a problem, occurring in every fifth patient. In our experience, the introduction of intraoperative PTH measurement has helped to lower the rates of persistence and recurrence. Further reductions in the recurrence rate might be achieved with novel, more accurate pre- and intraoperative imaging techniques.